Efektivitas dan Keberlanjutan Program CSR Penyediaan Air Bersih oleh PT Semen Padang di Kelurahan Baringin Kecamatan Lubuk Kilangan Kota Padang - Wulan Oktaviani; Intan Slipilia (YASIN, 2026)
The availability of clean water is a basic need that plays an important role in supporting public health, welfare, and quality of life. However, access to clean water remains a problem in several regions, particularly in areas with geographical conditions that are difficult to reach. In this context, corporate Corporate Social Responsibility (CSR) programs can serve as strategic instruments to help address social problems based on local needs. This study aims to analyze the effectiveness of PT Semen Padang’s Clean Water Provision CSR Program in Baringin Urban Village, Lubuk Kilangan Subdistrict, Padang City, as well as to identify the supporting factors, inhibiting factors, and sustainability of the program. This study used a qualitative approach with a descriptive method. Data were collected through interviews, observation, and documentation, and were then analyzed using the Miles and Huberman model with a Results-Based Monitoring and Evaluation (RBM) approach. The results showed that the program was effective in terms of input, activities, output, outcome, and impact. This program succeeded in providing clean water infrastructure that facilitated community access, reduced costs and effort, and supported improvements in cleanliness and quality of life. The success of the program was supported by corporate funding, the availability of water sources, and active community participation. However, service coverage remains limited due to geographical conditions and water distribution capacity that has not yet reached all target communities. This program also demonstrates good sustainability through community-based self-management and a maintenance fee system. The conclusion of this study confirms that PT Semen Padang’s Clean Water Provision CSR Program provides tangible and sustainable benefits for the community. This finding contributes to strengthening CSR practices based on local needs and provides practical implications for companies, communities, and stakeholders in designing effective, participatory, and sustainable social empowerment programs.